add 3.7 and 4.45 make sure to change it back to standard you'll get 815000000000000000000. move decimal between first and second digit which means you moved it to the left 18 times and your answer will be 8.15 x 10 ^18 I hope its right :( please don't judge if wrong :((( lol
Answer: 8.15 x 10²⁰
Step-by-step explanation:
In order to add or subtract, they must both have the same power - think of the power as "like terms". In this problem they already have the same power (10²⁰) so we don't need to manipulate them to have the same power. We can just add their coefficients (3.7 and 4.45).
3.7 x 10²⁰
+ 4.45 x 10²⁰
8.15 x 10²⁰
Theo's mom bought an 8 pack of juice boxes at the store for $4. Find the unit rate for the juice boxes
The ratio of cats to dogs seen by a veterinarian on one day is 2 to 5. If the vet saw 40 dogs in one day how many cats did he see
Answer:
He sees 16 cats that day
Step-by-step explanation:
If the veterinarian sees 5 dogs a day then he also sees 2 cats.
If he sees 40 dogs a day then,
⇒[tex]\frac{2}{5} *40[/tex]
=[tex]16[/tex] Cats
He sees 16 cats that day.
The correct option is C.
Approximately 29 dogs were seen by the vet in one day.
To solve this problem, we first need to find the fraction of dogs among the total animals seen by the vet.
Given that the ratio of cats to dogs is 2 to 5, the total parts in this ratio is 2 + 5 = 7.
Now, to find the fraction representing dogs, we divide the number of parts representing dogs (5) by the total parts (7). This gives us 5/7.
Next, to find out how many of the 40 animals were dogs, we multiply the total number of animals seen (40) by the fraction representing dogs:
40 animals × (5/7) = (40 × 5) / 7 = 200/7 ≈ 28.57
Since we're looking for an approximation, we round this to the nearest whole number, which is 29.
So, approximately 29 of the animals seen were dogs, which corresponds to option C.
The complete question is here:
The ratio of cats to dogs seen by a vet in a day is about 2 to 5. If a vet saw 40 animals in one day, about how many were dogs?
A. 5
B. 12
C. 29
D. 40
I have the picture of the equation.
find (f+g)(x)=
find (f-g)(x)=
find (f·g)(x)=
[tex]f(x)=\dfrac{5x+7}{7x-5},\ g(x)=\dfrac{8x}{7x-5}\\\\(f+g)(x)=f(x)+g(x)=\dfrac{5x+7}{7x-5}+\dfrac{8x}{7x-5}=\dfrac{5x+7+8x}{7x-5}=\dfrac{13x+7}{7x-5}\\\\(f-g)(x)=f(x)-g(x)=\dfrac{5x+7}{7x-5}-\dfrac{8x}{7x-5}=\dfrac{5x+7-8x}{7x-5}=\dfrac{-3x+7}{7x-5}\\\\(f\cdot g)(x)=f(x)\cdot g(x)=\dfrac{5x+7}{7x-5}\cdot\dfrac{8x}{7x-5}=\dfrac{(5x+7)(8x)}{(7x-5)(7x-5)}\\\\=\dfrac{40x^2+56x}{(7x)(7x)+(7x)(-5)+(-5)(7x)+(-5)(-5)}=\dfrac{40x^2+56x}{49x^2-70x+25}[/tex]
A car drives at a speed of 90km/h for 2 hours and 20 mins how far does the car travel
Final answer:
The car travels approximately 210 kilometers in 2 hours and 20 minutes by multiplying its speed of 90km/h by the time duration converted to hours (2.333 hours).
Explanation:
The student's question involves calculating the distance a car travels at a constant speed over a given period of time. In this case, the car drives at a speed of 90km/h for 2 hours and 20 mins. To find the distance, you can use the formula: distance = speed × time. First, convert 2 hours and 20 mins into hours, which is 2 hours + 20/60 hours = 2.333 hours.
Next, multiply the speed by the time to get the distance:
Distance = 90km/h × 2.333 hours = 209.97 km
So, the car travels approximately 210 kilometers in 2 hours and 20 minutes.
What is the remainder when the polynomial 5x2+10x−15 is divided by x + 5? Enter your answer in the box.
There are two ways you can approach this:
1) Factor [tex]\frac{5(x-1)(x+3)}{x+5}[/tex] this equals to [tex]\frac{5x^2+10x-15}{x+5}[/tex]
2) or divide which equals to 5x+35+[tex]\frac{160}{x+5}[/tex]
A single person earns a gross biweekly salary of $840 and claims 5 exemptions. What is the person's net pay. a. It is the same as the gross pay. b. It is $11 more than the gross pay. c. It is $11 less than the gross pay. d. It is $13 less than the gross pay.
Answer:
D. It is $13 less than the gross pay.
Step-by-step explanation:
To find the net pay, you have to look at the table h
We are given that table.
Step 1: Biweekly gross salary is $840 and the number of claimed is 5.
Step 2: Look for claimed number to the corresponding wage $840. It is 13, which is rounded by blue circle in the given table.
Thank you.
Answer:
D. It is $13 less than the gross pay.
Step-by-step explanation:
To find the net pay, you have to look at the table h
We are given that table.
Step 1: Biweekly gross salary is $840 and the number of claimed is 5.
Step 2: Look for claimed number to the corresponding wage $840. It is 13, which is rounded by blue circle in the given table.
Thank you.
i copied the other dued lol
A group of 485 people take a canoe trip. They fill up all avalible canoes that each hold 3 people with 273 people. The rest of the group will ride in canoes
that each hold 2 people. How many canoes will the group need? Write equations with unknown to show your steps.
Answer:
They will need 197 canoes.
Step-by-step explanation:
The first step is to find the ''3-people canoes'' that they filled.
Given that 273 people filled a certain number ''a'' of canoes that each hold 3 people, we know that is we multiply the number of canoes ''a'' by the number of people that can each canoe hold, we will obtain the number of people who
will take the canoe trip in the ''3-people canoes''. We write :
[tex]3a=273[/tex] ⇒
[tex]a=\frac{273}{3}=91[/tex]
We find that [tex]a=91[/tex] canoes. This means that 91 ''3-people canoes'' were filled each one with 3 people in order to hold 273 people in total.
The second step is to find the remaining people that won't take the ''3-people canoes''. We do this by subtracting 273 people to the total 485 people.
[tex]485-273=212[/tex]
We know that 212 people will travel in the ''2-people canoes''. Using a similar reasoning and defining as ''b'' to the total number of ''2-people canoes'' we write :
[tex]2b=212\\b=\frac{212}{2}=106\\ b=106[/tex]
We find that [tex]b=106[/tex] canoes is the total number of ''2-people canoes'' that we need If we want them to be filled up with 212 people.
The total number of canoes that the group will need is the sum of ''3-people canoes'' and ''2-people canoes'' :
[tex]Total=a+b=91+106=197[/tex]
The group of 485 people will need 197 canoes.
Sue is placing cookies in bags. She has 10 peanut butter cookies and 16 oatmeal cookies. She will place the same number of cookies in each bag and there will be only one type of cookie in each bag. If sue places the greatest number of cookies possible in each bag, how many bags will she need?
Write y= -4x² -16x -14 in vertex form.
A) y= -4(x-16)² -14
B) y= 4(x+4)² +2
C) y= -4(x+2)² +2
D) y= (x+2)² -14
B and D are both wrong. B has +4 outside the brackets. It is - 4
D is wrong because there is no 4 of any kind outside the brackets.
A is incorrectly represented inside the brackets as 16. That's not right
That only leaves C. <<<< Answer
Graphs
Notice that the red parabola and the green one are the same thing.
Red: y = -4x^2 - 16x - 14
Green: y = -4(x + 2)^2 + 2
Which of the following is the simplified form of the expression -x(x - y) + 4xy - x2?
A.2x2 - 3xy
B.-2x2 + 3xy
C.-2x2 + 5xy
D.2x2- 5xy
THIS one u probably have to choose more than one
Replace [tex]a_{n}[/tex] with 27, solve for [tex]a_{n-1}[/tex], and see if the result is a whole number.
27 = 2a ⇒ [tex]\frac{27}{2}[/tex] = a not a whole number NO
27 = 2a + 1 ⇒ 26 = 2a ⇒ 13 = a 13 is a whole number YES
27 = 3a ⇒ 9 = a 9 is a whole number YES
27 = 3a + 6 ⇒ 21 = 3a ⇒ 7 = a 7 is a whole number YES
27 = 3a + 1 ⇒ 26 = 3a ⇒ [tex]\frac{26}{3}[/tex] = a not a whole number NO
Answer: B, C, D
HELP ASAP PLEASE!!!
When we measure something, we do not have specify what units we are measuring in.
A. True
B. False
Answer:
B- False
Step-by-step explanation:
that is very false bc the units mean alot
A music store sold 300cds and 100cd players. If each cd cost $12 and each cd player cost $35, what was the store total earnings
So with what we know we can set up two equations to solve for the CDs and the players.
$12(300) = total earnings for cds
= $3600 total cds sold
$35(100) = total earnings for cd players
=$35000
add both of the totals of the CDs and the CD players to get the total earnings
$3600+$3500 = $7100 gained in total from both products sold
Check all of the polynomial functions that have 2 as a root.
A. h(m) = 8 – m^3
B. f(g) = g^3 – 2g^2 + g
C. f(a) = a^3 – 4a^2 + a + 6
D. f(x) = x^3 – x^2 – 4
A,C,D those were the answers i put and they were correct.
Answer:
A. h(m) = 27 – m3
C. f(a) = a3 – 4a2 + a + 6
D. f(x) = 2x3 – 5x2 – 9
Step-by-step explanation:
did review on edg2020
Evaluate:
6!
A.
60
B.
120
C.
360
D.
720
[tex]n!=1\cdot2\cdot3\cdot...\cdot n\\\\6!=1\cdot2\cdot3\cdot4\cdot5\cdot6=720\\\\Answer:\ \boxed{D.\ 720}[/tex]
Answer: D.
720
Step-by-step explanation:
We know that the value of n factorial or n! is given by :-
[tex]n!=n\times(n-1)\times(n-2)\times(n-3)\times...........................\times1[/tex]
We are given to find the value of 6! (or 6 factorial )
Using the above formula , the value of 6! is given by :-
[tex]6!=6\times(6-1)\times(6-2)\times(6-3)\times\times(6-4)\times(6-5)\\\\\Rightarrow\ 6!=6\times5\times4\times3\times2\times1\\\\\Rightarrow\ 6!=720[/tex]
Therefore , the value of 6! = 720
if(x)=x/2-3 and g(x)=4x2+x-4 find (f+g)(x)
[tex](f+g)(x)=4x^2+\frac{3}{2}x-7[/tex]
Answer:
[tex]h(x)=4x^2+\dfrac{3}{2}x-7[/tex]
Step-by-step explanation:
Given:
[tex]f(x)=\dfrac{x}{2}-3[/tex]
[tex]g(x)=4x^2+x-4[/tex]
To find: (f+g)(x)
It is a composite function. Sum of f and g function.
[tex]h(x)=f(x)+g(x)[/tex]
[tex]h(x)=\dfrac{x}{2}-3+4x^2+x-4[/tex]
Combine the like term
[tex]h(x)=4x^2+\dfrac{3}{2}x-7[/tex]
Hence, The sum of f(x) and g(x) would be [tex]h(x)=4x^2+\dfrac{3}{2}x-7[/tex]
Which expression is the completely factored form of 27x^3+y^6
Answer:
your answers C
Step-by-step explanation:
The factored form of the expression [tex]27x^3+y^6[/tex] is [tex](3x+y^2)(9x2-3xy^2+y^4)[/tex]. The correct answer of the factored expression is option A
Given the expression;
[tex]27x^3+y^6[/tex]
This can be expressed as the sum of cubes
[tex]a^3+b^3=(a+b)(a^2-ab+b^2)[/tex]
The given expression can also be written as the sum of cubes as shown:
[tex]27x^3+y^6 = (3x)^3+(y^2)^3[/tex]
We can see that:
a = 3x
b = y²
Substituting the given parameters into the formula above;
[tex]a^3+b^3=(a+b)(a^2-ab+b^2)\\(3x)^3+(y^2)^3=(3x+y^2)((3x)^2-3xy^2+(y^2)^2)\\(3x)^3+(y^2)^3=(3x+y^2)(9x2-3xy^2+y^4)\\[/tex]
Hence the factored form of the expression is [tex](3x+y^2)(9x2-3xy^2+y^4)[/tex]
Learn more here: https://brainly.com/question/7414037
A and B are two events.
Let P(A)=0.5 , P(B)=0.25 , and P(A and B)=0.15 .
Which statement is true?
A and B are not independent events because P(A|B)≠P(A) .
A and B are not independent events because P(A|B)=P(A) and P(B|A)=P(B) .
A and B are independent events because P(A|B)=P(B) and P(B|A)=P(A) .
A and B are not independent events because P(A|B)=P(B) and P(B|A)=P(A) .
Answer:
A and B are not independent events because P(A|B)≠P(A)
is the correct answer.
Step-by-step explanation:
If A and B are independent then we must have
P(AB) = P(A) P(B) and also
P(A/B) = P(A)
We are given that
A and B are two events.
Let P(A)=0.5 , P(B)=0.25 , and P(A and B)=0.15 .
P(A/B) = P(AB)/P(B) = 0.15/0.5 = 0.3
i.e. P(A/B) is not equal P(A)
Similarly P(B/A) = P(AB)/P(A) = 0.15/0.25 = 0.6 not equal to P(B)
Hence A and B are not independent.
Answer:
Step-by-step explanation:
A and B are not independent events because P(A|B)≠P(A)
is the correct answer.
How to know what to do next in a geometry two column proof?
To do a two-column proof, you must know the definitions of the terms that are being used. Also, you must know the postulates and theorems you have learned so far. You look at the given information, and using the definitions, postulates, and theorems, you reason in your mind how to go from the given to the conclusion, step by step. You write each step and the accompanying reason that allows you to conclude each step.
A segment has a midpoint or ray AB is the name of ray
T T—>T
T F—>T
F T —>T
F F—>F
answer is TT->T or a
Answer:
A)
Step-by-step explanation:
Please try to answer quickly :) thanks
Doughnuts are sold in bags anf cartons a bag holds 4 doughnuts and a carton holds ten doughnuts. Tom buys b bags of dougnuts and c cartons of doughnuts he buys a total of t doughnuts. Erite down a formula for t in terms of b and c
The formula is
T=4B+10C
What is the midpoint of ?
point M
point N
point P
point Q
Answer:
the answer is point N
Step-by-step explanation:
i dont have a graph to explain
The midpoint of a line segment is calculated using the formula Midpoint = ((x1 + x2)/2 , (y1 + y2)/2), which finds the average of the x-coordinates and y-coordinates of the two points. Unfortunately, without specific points, we can't provide a concrete midpoint.
Explanation:Unfortunately, your question is slightly unclear as we need more detail to accurately determine the midpoint of the segment. Generally, if you want to find the midpoint of a segment, you need two defined points. Knowing these two points, you can calculate the midpoint using the formula: Midpoint = ((x1 + x2)/2 , (y1 + y2)/2). This formula calculates the average of the x-coordinates and y-coordinates of the two points, which gives you the coordinates of the midpoint.
Learn more about Midpoint Calculation here:https://brainly.com/question/34219741
#SPJ2
The total daily cost (in dollars) of manufacturing scented candles is given by the function C(b) = 250 + 3b, where b is the number of candles manufactured. Which function represents the average manufacturing cost, A, in terms of b?
The average total cost of manufacturing scented candles is given by the formula A(b) = C(b)/b = (250 + 3b)/b, where b is the number of candles manufactured.
Explanation:The concept of average total cost is key in the calculation. Given the function for total cost of the candles, C(b) = 250 + 3b, the average cost, A, can be calculated by dividing the total cost by the number of candles, b. Therefore, the function representing the average cost, A, in terms of b is given by A(b) = C(b)/b = (250 + 3b)/b. It's important to note that this function also signifies the 'economies of scale', stating as output number increases, the average cost falls.
Learn more about Average Total Cost here:https://brainly.com/question/15071280
#SPJ12
The underwater Terror toller-coaster tide takes passengers up to a 123 feet above ground. It then quickly drops the riders 154 feet into a underwater passageway. Next, the coaster immediately takes everyone straight up again 187 feet before it drops 175 feet into the second underwater passageway. What is the elevation of the 2nd underwater passageway relative to the ground? Please show your work.
up (+) 123 187
down (-) -154 -175
(123 + 187) - (154 + 175)
= 310 - 329
= -19
Answer: 19 feet below ground
find the 26 term is a1=30 and d =-2
Answer:
[tex]a_{26}=-20[/tex]
Step-by-step explanation:
The formula of a nth term of an arithmetic sequence:
[tex]a_n=a_1+(n-1)d[/tex]
We have:
[tex]a_1=30,\ d=-2,\ n=26[/tex]
Substitute:
[tex]a_{26}=30+(26-1)(-2)=30+(25)(-2)=30-50=-20[/tex]
How long is the piece of string?
Answer:
C) 14 units
Step-by-step explanation:
The equation is in standard form, so the larger denominator is the square of the semi-major axis. That length is √49 = 7, so the major axis length is 2·7 = 14. This length is the length of the string.
x^2+50=0
What are the solutions to the equation over the complex numbers?
x=
or
x=
ANSWER= +/- 5i sqrt2
sqrt=square root sign to solve you subtract 50 so x^2=-50 then get the square root on both sides and you're left with x=5isqrt 2 the i comes from the negative sign inside the square root
+/- 5i sqrt2 is the solution
Solve for x.
2x^2-4x=0
Hey there!!
Equation given :
2x² - 4x = 0
Taking the common terms
2x ( x - 2 ) = 0
Divide by 2x on both sides
x - 2 = 0
Adding 2 on both sides ...
x = 2
And another answer would be zero as the whole equation is zero,
Hence the answer : ( 0 , 2 )
Hope it helps@+!!
The value x for equation 2x² - 4x = 0 is 2.
Given equation:
2x² - 4x = 0
Add 4x on both side,
2x² = 4x
Divide x on both side
2x = 4
Divide 2 on both side,
x = 2.
Therefore, the value x for equation 2x² - 4x = 0 is 2.
Learn more about equation here:
https://brainly.com/question/20094734
#SPJ6
6. Mike and his best friend Dan have the same birthday, but Mike is three years older than Dan. Let the variable x represent Mike's age and y represent Dan's age. Which graph represents the relationship between Dan's age and Mike's age?
also can anyone tell me all the answers for Solving Equations Unit Test please I really need the help.
Answer:
A linear graph will be plotted to show the relation between ages of Mike and Dan.
Step-by-step explanation:
As the age of Mike increase, the age of Dan will also increase. There is a relation of direct proportionality and a linear graph line will be plotted. When x=3, y=0, therefore the line will be at a distance of 3 x-intercept from origin.